2018
DOI: 10.21276/ap.2018.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of anticancer drugs and its prevention with special reference to role of garlic constituents

Abstract: Cancer is the leading cause of death globally. World Health Organisation (WHO) reported that 70% of death caused by cancer occurs in low or middle income countries which may be due to unavailability of correct treatment or delayed medical support. Despite of different therapies available to cure the cancer or to prolong the life of cancer survivors; chemotherapy is still central to cancer therapy. Administration of chemotherapeutic drugs either independently or in combination with other therapies such as irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Garlic has been indicated to mitigate the adverse effects of several anticancer therapies [127]. In one study, AGE improved the renal histological, ultrastructural, and biochemical changes induced by cisplatin therapy, such as hemorrhaging, glomerular atrophy, tubular necrosis, and degeneration in adult male rats [128].…”
Section: Biological Functions Of Garlicmentioning
confidence: 99%
“…Garlic has been indicated to mitigate the adverse effects of several anticancer therapies [127]. In one study, AGE improved the renal histological, ultrastructural, and biochemical changes induced by cisplatin therapy, such as hemorrhaging, glomerular atrophy, tubular necrosis, and degeneration in adult male rats [128].…”
Section: Biological Functions Of Garlicmentioning
confidence: 99%
“…Under various physiological conditions NF-κB and COX-2 participate in the regulation of cell signaling and play a critical role in CP-induced AKI in mice 26 . It has been reported that the NF-κB pathway depending on the degradation of IκB becomes activated with CP treatment and increases the release of inflammatory cytokine series including TNF-α, IL-1β and TGF1β 27 . It is also reported that the upregulation of IL-6 is the hallmark of activation of NFκB signaling and inflammation 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Garlic has negative effect against linoleic acid by increasing the effect of eicosatetraenoic acid, which is a breast cancer suppressor [52]. Probability of hormone receptive cancer is repressed by Sulfur compounds of garlic such as allyl-sulfides because of its aquaphobic environment and estrogen receptors with cysteine residue in hormone binding [53]. Different studies have been done which proves garlic and organic allyl Sulfur elements has capability to prevent cancer process.…”
Section: Anti-carcinogenic Effect Of Garlicmentioning
confidence: 99%